The inquisitive mindset and the Qur’anic ethos: an exploration into Islamic inquisitiveness = Dasar pemikiran inkuisitif dan nilai-nilai etika dalam Quran: penerokaan ke dalam inkuisitif Islam - Badi, Jamal Ahmed Bashier; Machouche, Salah (IIUM Press, International Islamic University Malaysia, 2018)
The Qur’anic Ethos stresses the importance of an inquisitive mindset. The aim of this paper is to show the depth of theoretical information and practical advice the Qur’an provides, in regards to fostering and nurturing an inquisitive Mindset. This article will elaborate on the Qur’anic teachings on inquisitiveness. There are more than one thousand two hundred questions in the Qur’an, which are analysed to examine their contribution to fostering inquisitive thinking. The multiple characteristics of an inquisitive mindset are explained by recourse to several prominent classical exegetists. The Qur’anic blueprint for inquisitive learning is sketched briefly with an excursion into the etiquettes of inquisitiveness. A practical application of the theoretical discussion of inquisitiveness is provided in the context of recovering the Khaldūnian Legacy in sociology. The article concludes that fostering inquisitiveness is of the utmost importance, especially in our (post) modern times. It is hoped that the article will show, with innumerable evidence, that the Qur’an is a rich source for finding methods on developing an individual’s inquisitive mindset.